The impact of the SARS-CoV-2 pandemic on the workloads of UPMC advanced radiotherapy centers in Italy - Forte, Velia; Di Minico, Debora; Cavallo, Francesca; Gennuso, Natascia; Caponigro, Stefania; Borrelli, Simona; Nicolini, Leonardo; Lusini, Federica; Triscari, Giulia; Canino, Claudia; Capone, Luca; Allegretta, Sara; et al. (Journal of Biomedical Practitioners, 2021)
GOALS The Advanced Radiotherapy Centers of UPMC San Pietro FBF of Rome (CC#1) and UPMC Villa Maria of Mirabella Eclano (CC#2) conducted a study to review variations in department workloads and workflows experienced during the pandemic. The potential relation between these variations and the new procedures introduced to prevent and contain the COVID-19 infection was also studied. MATERIALS AND METHODS The data used were obtained from reports present in the ARIA® system (v. 15.1 Varian Medical Systems, Palo Alto, CA, U.S.A.). To examine the workloads was used the Downtime, an indicator that directly quantifies the inactivity of the department, derived from the ratio between the daily stand-by time of the LINACs (TrueBeam STx®, Varian Medical Systems, Palo Alto, CA, U.S.A.) and the mean number of treatments performed every day. In order to examine the workflows and possible delays, we measured the time between the treatments ("Therapy intervals"). RESULTS The Downtime average at CC#1 slightly increased from 3.1% in 2019 to 3.8% in 2020. However, the monthly analysis shows significant reduction (March-April-May) and increase (November-December) peaks. At CC#2, the 2020 Downtime trend was fairly consistent (average value: 3.3%), with an increase during the first wave of the pandemic. The "5-10 min" Therapy intervals at CC#1, reviewed comparing the March-April-May 2020 quarter with 2019, were higher in the first months and lower in May; the "10-15 min" intervals were stable; the ">20 min" intervals slightly increased in March 2020. At CC#2, the trend in 2020 decreased during the months of higher health care emergency and increased during the summer months. CONCLUSIONS The fact that the trends of the indicators show peaks only during the periods of major health care emergency indicates an impact of the pandemic, both on the workload and on the workflow. However, they also highlight the staff's ability to rapidly adapt to the new procedures, without affecting the overall performance of the both centers.